RANCANG BANGUN ALAT PEMANTAU DETAK JANTUNG DAN KADAR OKSIGEN DENGAN SISTEM PERINGATAN BERDASARKAN USIA PENGGUNA - Agung Suburdjati, Bacilius; Andini Ismayanti, Rosa; Kenneth Setiadi, Benedictus; Herdiana, Oding (Jurnal Sistem Informasi Galuh, 2025)
Cardiovascular health and blood oxygen levels are critical indicators for monitoring a person's physical condition, especially during activities or exercise. Monitoring these two parameters is essential to ensure that an individual remains within safe limits to continue physical exertion. Therefore, a portable device capable of accurately and in real-time measuring blood oxygen saturation (SpO₂) and heart rate (BPM) is required. This study aims to design and develop a pulse oximeter device based on the Arduino Uno microcontroller using the MAX30102 sensor, equipped with LED indicator lights and a keypad as a user input interface. Users can input their age through the keypad, and the system calculates their maximum BPM as a safe threshold for physical activity. The LED lights serve as visual indicators to signal whether the user's SpO₂ and BPM values are within the normal range. Testing results show that the device is capable of measuring blood oxygen saturation with an accuracy of 99.97% and heart rate with an accuracy of 98%. With its compact size, this device has the potential to be used practically in various situations, both by individuals and healthcare personnel for preliminary health monitoring.